Pengaruh Risiko Investasi Terhadap Return Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Chaerunnisa Rumianti (Jurnal Mirai Management, 2023)
The purpose of this study was to test and analyze the effect of investment risk on stock returns in manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 - 2021. The data collection uses secondary data obtained from the company's financial statements available on the Indonesia Stock Exchange for the period 2019 - 2021. The population used in this study is In this study, there were 26 manufacturing companies in the food and beverage sub- sector. With a research sample of 34 sample data. The results of the research variable data have been tested for classical assumptions in the form of normality, heteroscedasticity and autocorrelation assumptions tests. The method of data analysis used a simple linear regression analysis technique. The results showed that the investment risk had a negative and insignificant effect on stock returns. Keywords: investment risk and stock return